Efek Antihelmintik Ekstrak Akar Ceguk (Quisqualis indica, L.) pada Ascaris suum, Goeze in Vitro - Kurnia, Antonius Bagus Budi; Haryati, Sri; Sakiman, Bambang Sukilarso (Nexus Biomedika, 2013)
Background: Radix-Quisqualis indica L. contains saponins and potassium quisqualata that are known having anthelmintic effect. This study aimed  to determine the effect of extract of radix-Quisqualis indica L. toward mortality of Ascaris suum, Goeze  in vitro Methods: This study was a laboratory experimental research using the post-test only controlled group design. Subjects were adult Ascaris suum, Goeze. The sampling technique used was purposive sampling. Subjects were arranged into 7 groups, each group consisted of 4 worms, replications were performed 4 times. Saline solution was used in negative control group and pyrantel pamoate 5 mg/ml was used in positive control group, while the treatment group was treated with extract of radix-Quisqualis indica, L. at concentration of 50%, 60%, 70%, 80%, and 90%. Subjects  were immersed in 25 ml of  test solution and incubated at 37°C. Observations were done every 1 hour and the numbers of dead worms were counted. Data were analyzed with linier regression and probit analysis. Results: The result of observation showed that mean time of total death of Ascaris suum, Goeze  in the negative control and in the positive control were 96.00 hours and 1.25 hours, each. While mean time of total death of Ascaris suum, Goeze in the extract of radix-Quisqualis indica, L. at concentration of 50%, 60%, 70%, 80%, 90% were 11.50 hours, 9.50 hours, 8.00 hours, 5.75 hours and 3.50 hours, consecutively. Shapiro Wilk test showed that the distribution of the data was normal (p > 0.05). Linear regression test showed that the variation of the extract concentration affected time of worm death. Probit analysis showed that LC50 and LT50 of the extract of radix-Quisqualis indica L. were 69.80% and 3.90 hours. Conclusions: The extract of radix-Quisqualis indica, L. affected mortality of Ascaris suum, Goeze  in vitro. Keywords: extract of radix Quisqualis indica, L., Ascaris suum, Goeze,